2022
DOI: 10.32635/2176-9745.rbc.2022v68n3.2566
|View full text |Cite
|
Sign up to set email alerts
|

O Impacto da Pandemia da Covid-19 no Volume de Mamografias no Brasil: uma Análise de Previsão Baseada nos Números Históricos

Abstract: Introdução: A neoplasia mamaria constitui a primeira causa de óbito por câncer em mulheres brasileiras. Dados sobre o real impacto da pandemia na política de rastreamento e diagnostico do câncer de mama no Brasil ainda são desconhecidos. Objetivo: Avaliar o efeito da pandemia da covid-19 no número de mamografias realizadas no Sistema Único de Saúde (SUS). Método: Estudo epidemiológico, quantitativo e de delineamento transversal. Foram selecionadas mamografias mensais realizadas no SUS após consulta ao Departam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Analyses of the effect of the pandemic on breast cancer screening in Brazil, through the registration of mammograms, observed a reduction in the total number of this procedure performed in the pandemic period. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Analyses of the effect of the pandemic on breast cancer screening in Brazil, through the registration of mammograms, observed a reduction in the total number of this procedure performed in the pandemic period. 12 …”
Section: Discussionmentioning
confidence: 99%
“…A factor of great impact in recent years has been the pandemic caused by COVID-19, which has reflected on the performance of examinations and surgical procedures worldwide [ 22 ]. The results of the authors Demarchi et al [ 23 ], who analyzed a decrease of 1,705,475 mammograms in Brazil in the year 2020 alone, show a reduction of about 40% in relation to the previous year.…”
Section: Discussionmentioning
confidence: 99%
“…17 Other studies that have analyzed the impact of the COVID-19 pandemic on cancer screening tests in Brazil have identified that screening actions have been affected, generating a considerable decrease in the number of screening tests, mammography, PSA and cytopathological tests, which should translate into an increase in cases of advanced disease, with serious negative consequences for patients and the health system. 18,19 This highlights the importance of nurses in disseminating information capable of encouraging and favouring the adoption of healthy habits and lifestyles, as well as their importance in providing guidance on the signs and symptoms of this neoplasm in a clear and accessible way to the reality experienced, i.e. carrying out health education activities in the community.…”
Section: Introductionmentioning
confidence: 99%